PENERAPAN PEER ASSISTED LEARNING TERHADAP PENGUASAAN KETERAMPILAN BERMAIN FUTSAL PADA EKSTRAKURIKULER DI SMA NEGERI 19 BANDUNG - Ilham Nurul Alam, - (2020)
The purpose of this study was to test the application of peer assisted learning mastery to futsal playing skills in extracurricular activities at 19 Bandung Senior high school. (experimental study on extracurricular activities at 19 Bandung Senior high school). The method used is a quasi-experimental method using a pretest posttest group design. The population in this study were students who took futsal extracurricular activities at 19 Bandung Senior high school. The sample used was 20 students who were active in futsal extracurricular activities at 19 Bandung Senior high school. The research instrument used was the student activity observation sheet, playing skills using the Game Performance Assessment Instrument (GPAI). In the diagram it can be seen that the average value obtained during the pre-test (initial test) is 0.61 and the post-test (final test) is 0.71, the increase in the average value indicates that after being given treatment using Peer assisted learning has increased the skills of playing futsal in futsal extracurricular activities at 19 Bandung Senior high school.